Status of PSMA-targeted radioligand therapy in prostate cancer: current data and future trials - Albert Jang; Ayse T. Kendi; Oliver Sartor (Therapeutic Advances in Medical Oncology, 2023)
Metastatic prostate cancer continues to be an incurable disease. Despite all the novel therapies approved in the past two decades, overall patient outcomes remain relatively poor, and these patients die on a regular basis. Clearly, improvements in current therapies are needed. Prostate-specific membrane antigen (PSMA) is a target for prostate cancer given its increased expression on the surface of the prostate cancer cells. PSMA small molecule binders include PSMA-617 and PSMA-I&T and monoclonal antibodies such as J591. These agents have been linked to different radionuclides including beta-emitters such as lutetium-177 and alpha-emitters such as actinium-225. The only regulatory-approved PSMA-targeted radioligand therapy (PSMA-RLT) to date is lutetium-177–PSMA-617 in the setting of PSMA-positive metastatic castration-resistant prostate cancer that has failed androgen receptor pathway inhibitors and taxane chemotherapy. This approval was based on the phase III VISION trial. Many other clinical trials are evaluating PSMA-RLT in various settings. Both monotherapy and combination studies are underway. This article summarizes pertinent data from recent studies and provides an overview of human clinical trials in progress. The field of PSMA-RLT is rapidly evolving, and this therapeutic approach will likely play an increasingly important role in the years to come.